1991
DOI: 10.1007/bf00167884
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and Peters' anomaly

Abstract: A 26-year-old black woman with Peters' anomaly who had been followed since early childhood developed an open-angle form of glaucoma, which required filtering surgery. Light and electron microscope studies of the trabeculectomy specimen, which was obtained by en bloc resection of the trabecular meshwork and iridectomy specimen, revealed that the structures of the anterior-chamber angle were grossly normal aside from evidence of premature aging on the basis of abundant broad-banded collagen fibers in the trabecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Approximately half of patients with Peters anomaly develop glaucoma, and glaucoma secondary to Peters anomaly is an important complication that can affect visual prognosis [6,7,10]. In this study, VA was significantly poorer for the eyes with glaucoma than for those without glaucoma.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Approximately half of patients with Peters anomaly develop glaucoma, and glaucoma secondary to Peters anomaly is an important complication that can affect visual prognosis [6,7,10]. In this study, VA was significantly poorer for the eyes with glaucoma than for those without glaucoma.…”
Section: Discussionmentioning
confidence: 50%
“…However, there were cases in which TLO was difficult to perform. Kupfer and Heath [7,9] revealed that the structures of the anterior chamber angle were grossly normal, aside from evidence of premature aging based on abundant broad-banded collagen fibers in the trabecular lamellae. However, Shields noted that a high insertion of the anterior uvea into the trabecular meshwork is a common finding in some cases of secondary childhood glaucoma [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory deprivation, amblyopia, and glaucoma are significant sequelae of Peters’ anomaly. 8 It is vital for the ophthalmologist to classify it as either Type 1 or Type 2, and to receive multiple consultations from neonatology and genetics pending a diagnosis following birth. 9,10 A later diagnosis recommends that patients undergo molecular genetic testing and receive consults from retina, cornea, and glaucoma specialists.…”
Section: Short Reportmentioning
confidence: 99%